Penerapan Analisis Dimensional Pada Perubahan Tekanan Udara Perangkat Oscillating Water Column (OWC) - Jahirwan Ut Jasron (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
Energy is a significant need in life in an increasingly sophisticated era. One of the renewable energy sources that are quite promising to be managed is ocean wave energy. An oscillating water column (OWC) is a device that can use to convert wave energy into mechanical energy, which can then convert into electrical energy. The energy harvesting process, in reality, involves many variables that influence each other and work simultaneously. Formulating n correlations between one variable and another group of variables can be solved by dimensional or statistical analysis. Dimensional analysis, in some instances, will be easier and relatively fast to find the results. The dimensional analysis used is the pi Buckingham method, and based on the results of the research obtained a correlation between the wave characteristics and the geometry of the air column on changes in air pressure in the OWC device column were the more significant the H/L and m/a2ρ, the greater the difference in air pressure in the column. This functional relationship has a good match with the results of the experiments carried out.